Laccase Production from Agrocybe pediades: Purification and Functional Characterization of a Consistent Laccase Isoenzyme in Liquid Culture - Paulina González-González; Saúl Gómez-Manzo; Araceli Tomasini; José Luis Martínez y Pérez; Edelmira García Nieto; Arely Anaya-Hernández; Elvia Ortiz Ortiz; Rosa Angélica Castillo Rodríguez; Jaime Marcial-Quino; Alba Mónica Montiel-González (Microorganisms, 2023)
Laccases are valuable enzymes as an excellent ecological alternative for bioremediation issues because they can oxidize persistent xenobiotic compounds. The production and characterization of extracellular laccases from saprotrophic fungi from disturbed environments have been scarcely explored, even though this could diversify their functional characteristics and expand the conditions in which they carry out their catalysis. Agrocybe pediades, isolated from a disturbed forest, produces an extracellular laccase in liquid culture. The enzyme was purified, identified and characterized. Copper and hexachlorobenzene do not function as inducers for the laccase produced. Partial amino acid sequences were obtained by LC-MS/MS that share similarity with laccases from other fungi. Purified laccase is a monomer with a molecular mass between 55–60 kDa and had an optimum activity at pH 5.0 and the optimum temperature at 45 °C using 2,6-dimethoxyphenol (2,6-DMP) as substrate. The Km and Vmax also determined with 2,6-DMP were 100 μM and 285 μmol∙min−1∙mg−1, respectively, showing that the laccase of A. pediades has a higher affinity for this substrate than that of other Agaricales. These features could provide a potential catalyst for different toxic substrates and in the future laccase could be used in environmental recovery processes.